The cosmology of ultralight scalar dark matter coupled to right-handed neutrinos - Ryan Plestid; Sophia Tevosyan (Journal of High Energy Physics)
Abstract We consider ultralight scalar dark matter that couples to right-handed neutrinos. Due to the high density of neutrinos in the early universe, the background neutrino density dominates the dynamics of the scalar field, and qualitatively alters the field’s cosmological evolution. This effect has not been included in previous literature, and changes the interpretation of cosmological data and its interplay with laboratory experiments. To illustrate these points a simplified model of a 1 + 1 setup with a single scalar field is analyzed. We find that: i) The scalar field experiences an asymmetric potential and its energy density redshifts differently than ordinary matter. ii) Neutrino mass measurements at the CMB and oscillation experiments performed today complement one another (i.e., they constrain different regions of parameter space). iii) There exists potentially interesting cosmologies with either O(1) variations in the dark matter density between the CMB and today, or O(1) oscillations of neutrino mass.